Satversmes 104.pants - problēmas praksē un iespējamie risinājumi. - Orēniša, Eva (Latvijas Universitāte, 2012)
Darbā apskatīts Satversmes 104.pantā garantēto personas tiesību apjoms likumā paredzētajā veidā vērsties valsts un pašvaldību iestādēs ar iesniegumiem un saņemt atbildi pēc būtības. Ievērojot pantā ietverto atsauci uz to, ka tiesības vērsties iestādē ir izmantojamas „likumā paredzētajā veidā”, darbā tiek pētīts Administratīvā procesa likuma, Informācijas atklātības likuma un it īpaši Iesniegumu likuma regulējums minēto tiesību aspektā. Pētījuma rezultātā tiek konstatēti vairāki ar likumu noteikti Satversmes 104.pantā paredzēto tiesību ierobežojumi. Daži no šiem ierobežojumiem atzīstami par neatbilstošiem Satversmei. Darbā veikta apjomīga tiesu prakses analīze, kas ļauj izdarīt secinājumus gan par Satversmes 104.panta tvērumu, gan Iesniegumu likuma regulējamo jautājumu loku, gan par Informācijas atklātības likumā un Iesniegumu likumā nepieciešamajiem uzlabojumiem.

The paper looks at the scope of the rights to everyone, as provided for by law, to address a petition to State or local government institutions and to receive a materially responsive reply guaranteed in the article 104 from Constitution of the Republic of Latvia. Considering the reference incorporated in article that the rights to address a petition to an authority must be exercised “as provided for by law”, paper looks at the regulation of Administrative Procedure law, Freedom of Information law and especially Law on Submissions from the legal aspect mentioned above. The paper concludes that a number of regulations provided by law in the article 104 from Constitution of the Republic of Latvia can be recognized as a limitation to individual's rights to address a petition. Research has admitted that such limitation is improper to Constitution of the Republic of Latvia. The paper looks at regulation in its practice. This analysis allows concluding the scope of the article 104 from Constitution of the Republic of Latvia, the scope of application of the Law on Submissions and necessary improvements in the Freedom of Information law and Law on Submissions.
Article 104 from Constitution of Republic of Latvia – problems in practice and possible solutions.
Keywords: Juridiskā zinātne